(untitled) (UNWE Yearbook, 2023)
The contemporary tourism industry is developing in an extremely dynamic environment, influenced by a global pandemic, hyper-competition, globalization and implementation of digital technologies. This heterogeneous in nature, but extremely structuring factor, motivates marketers to find new concepts, methods and models, through which to attract the attention of tourism consumers. Tourism companies face two significant challenges – how to understand customers’ needs and how to differentiate themselves from other tourism market competitors. The answer to these questions is in the understanding of the fundamental difference between the functioning and perception of a tourism company as a brand or as a trademark.